Responses of the Photosynthetic Electron Transport Reactions Stimulate the Oxidation of the Reaction Center Chlorophyll of Photosystem I, P700, under Drought and High Temperatures in Rice - Wada, Shinya (Int J Mol Sci, 2019)
It is of interest how photosynthetic electron transport (PET) reactions respond to excess light energy caused by the combination of drought stress and high temperatures. Since such information is scarcely available for photosystem I (PSI), this question was explored in rice (Oryza sativa L.) plants subjected to drought stress, using culture solutions that contain poly(ethylene glycol) at different concentrations under two day/night temperature regimes. At 27/22 °C (day/night), drought stress led to the oxidation of the reaction center of the chlorophyll of PSI (P700), and also led to decreases in the quantum efficiencies of photosystem II (PSII) and PSI, and a reduction of the primary quinone electron acceptor of PSI. Such drought stress responses were wholly stimulated at 35/30 °C. These parameters were strongly correlated with each other and were minimally affected by temperature. These results indicate that the drought stress responses of the respective PET reactions are closely associated with each other in the oxidization of P700 and that such responses are stimulated at high temperatures. The underlying mechanisms of these phenomena were discussed. While P700 oxidation is thought to suppress reactive oxygen species (ROS) production, PSI photoinhibition was observed under severe stress conditions, implying that P700 oxidation is not sufficient for the protection of PSI under drought stress.